Pengaruh Kualitas Dan Citra Merek Terhadap Keputusan Pembelian Hp Merek Vivo Y100: Studi Kasus Pada Mahasiswa/i STIE Bina Karya Tebing Tinggi - Ketaren, Abednego (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This research was conducted with the aim of finding out how quality and brand image influence the decision to purchase the VIVO Y100 brand cellphone among STIE Bina Karya Tebing Tinggi students. The independent variables of the research are quality and brand image, while the dependent variable is purchasing decisions. The results of hypothesis testing using multiple regression analysis with two independent variables and one dependent variable show that: Quality has no influence on the decision to purchase a VIVO Y100 brand cellphone among STIE Bina Karya students, brand image influences the decision to purchase a VIVO Y100 brand cellphone among students. i STIE Bina Karya, quality and brand image together influence the decision to purchase the VIVO Y100 Brand HP among STIE Bina Karya students.